Diverse Roles of Prostaglandins in Blastocyst Implantation - Naguib Salleh (The Scientific World Journal)
Prostaglandins (PGs), derivatives of arachidonic acid, play an indispensable role in embryo implantation. PGs have been reported to participate in the increase in vascular permeability, stromal decidualization, blastocyst growth and development, leukocyte recruitment, embryo transport, trophoblast invasion, and extracellular matrix remodeling during implantation. Deranged PGs syntheses and actions will result in implantation failure. This review summarizes up-to-date literatures on the role of PGs in blastocyst implantation which could provide a broad perspective to guide further research in this field.